Nikah Mut'ah Dalam Literatur Kitab Hadis - Marhumah, Ema (Musawa Jurnal Studi Gender dan Islam, 2002)
There are two hadith that discuss the issue of mut'ah marriage, one of them permits mut'ah marriage, while the other hadith forbids its existence. In terms of the legitimacy of hadith (takhrij hadith), both hadith demonstrate their validity, meaning that both hadith can serve as evidence in making laws. In the view of the writer, these two hadith cannot be separated. In the writer's analysis, they are related and in fact strengthen each other, in the way that eventually mut'ah marriage was prohibited. Hence the two hadith are not contradictory. What occurred was a nullification of the law of mut'ah marriage which was previously allowed, then was later forbidden. One law was repealed and replaced by a new one, making the old law legally null and void.